FROM CIVIL WAR TO BOKO HARAM: AN ANALYSIS OF THE MAJOR IMPEDIMENTS TO A SUCCESSFUL NATION BUILDING IN NIGERIA. (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
Since its independence on the 1st October, 1960, Nigeria’s effort to successful nation building had been greatly threatened by a combination of regional and tribal sentiments. Immediately after the nation’s independence, intra-regional and interregional rivalries, resulting from claims of discrimination and marginalization, brewed. Thus Within a span of seven months, two successful military coups were staged. The first was on the 15th January 1966 and the second in July of the same year. The events that followed led to Civil war 1967-70. The war, more than anything else threatened Nigeria’s internal security. Added to the lingering claims of marginalization and discrimination that followed the civil war, was political thuggery and manipulation of religion associated with the second republic and the successive military juntas. Religiously motivated aspiring groups such as Maitasine soon sprang up. While Nigeria was still recuperating from the scourge of the Maitastine crises, General Ibrahim Babangida registered Nigeria as member of the Organization of Islamic Countries (OIC). This generated a lot of friction among Nigerians. However, greater controversies began when President Ibrahim Babangida annulled the 1993 presidential elections. The wave of Sharia in the early days of fourth republic hit the nation’s unity badly. This was followed by growing ethno-religiousconflicts, organize kidnappings and banditry. It is lamentable that Nigeria survived all these crises and conflicts, but only to be threatened by a sectarian group, Boko Haram. Attempt, here is made, to historicize some of these crises frustrating Nigeria’s effort to a successful national development.